Assessment Report on the Tribal area of Balue, Kumba Division, Cameroons Province (Colonial Letters and the Contact of Knowledges, 1922)
This file contains colonial assessment report on Balue, Kumba Division
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies